2009
DOI: 10.1074/jbc.m808325200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Sphingolipid Metabolism by the Phosphatidylinositol-4-phosphate Phosphatase Sac1p through Regulation of Phosphatidylinositol in Saccharomyces cerevisiae

Abstract: Sphingolipids and phosphoinositides both play signaling roles in Saccharomyces cerevisiae. Although previous data indicate independent functions for these two classes of lipids, recent genetic studies have suggested interactions between phosphatidylinositol (PtdIns) phosphate effectors and sphingolipid biosynthetic enzymes. The present study was undertaken to further define the effects of phosphatidylinositol 4-phosphate (PtdIns(4)P) metabolism on cell sphingolipid metabolism. The data presented indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 48 publications
3
63
3
Order By: Relevance
“…Furthermore, the calcium sensitive phenotype of the csg2 complex sphingolipid biosynthesis mutant was suppressed by a mss4 ts mutation (Dunn et al, 1998). In contrast, inhibition of the plasma membrane PI4-kinase Stt4p by wortmannin resulted in an increase in complex sphingolipids (Brice et al, 2009). Similarly in the mss4-f12 mutant we observed reduced levels of PtdIns(4,5)P 2 and an accumulation of the complex sphingolipid, M(IP) 2 C. Furthermore, inhibition of complex sphingolipid biosynthesis results in an increase in plasma membrane PtdIns(4)P and PtdIns(4,5)P 2 (Jesch et al, 2010), suggesting that the increased PI levels observed in the mss4-f12 mutant are likely to contribute to increased complex sphingolipid levels.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the calcium sensitive phenotype of the csg2 complex sphingolipid biosynthesis mutant was suppressed by a mss4 ts mutation (Dunn et al, 1998). In contrast, inhibition of the plasma membrane PI4-kinase Stt4p by wortmannin resulted in an increase in complex sphingolipids (Brice et al, 2009). Similarly in the mss4-f12 mutant we observed reduced levels of PtdIns(4,5)P 2 and an accumulation of the complex sphingolipid, M(IP) 2 C. Furthermore, inhibition of complex sphingolipid biosynthesis results in an increase in plasma membrane PtdIns(4)P and PtdIns(4,5)P 2 (Jesch et al, 2010), suggesting that the increased PI levels observed in the mss4-f12 mutant are likely to contribute to increased complex sphingolipid levels.…”
Section: Discussionmentioning
confidence: 96%
“…3B, lane 1). Phosphatidylinositol is a component of complex sphingolipids in yeast, and it has been reported that sphingolipid metabolism is modulated by phosphatidylinositol levels regulated by Sac1 (Brice et al, 2009). Similarly to the response to myriocin, increased phosphorylation of Orm1 in sac1D cells might reflect a compensatory response to inhibited flux through the sphingolipid synthesis pathway.…”
Section: Orm1 Phosphorylation Responds To Orm2 Statusmentioning
confidence: 99%
“…Additionally, they share headgroup modifications, with glycerolipids often providing the headgroup moieties for sphingolipids. For example, the production of inositolphosphorylceramide (IPC) in yeast relies on inositol derived from phosphatidylinositol (PI), with the latter being converted to diacylglycerol (DAG) (Brice et al 2009). In mammalian cells, SM production is similarly coupled to conversion of phosphatidylcholine (PC) to DAG.…”
Section: Sphingolipid Homeostasis In the Er And Beyondmentioning
confidence: 99%